The Impact of the School Environment on Motivation for Physical Education Learning in Junior High Schools - Nurfadhilah, Muhammad Ilyas; Hambali, Sumbara; Hardi, Veny Juniarni (STKIP Paasundan Press, 2026)
This study addresses the issue of the impact of the school environment on students’ learning motivation in physical education at the junior high school level. The aim of this research is to determine the effect of the school environment on learning motivation in physical education among junior high school students. This research employed an ex post facto method with data collected through a questionnaire conducted at SMP Negeri 3 Padalarang. The population consisted of all students at SMP Negeri 3 Padalarang, and the sample was one class of 45 students selected using a cluster random sampling technique. The research instrument was a questionnaire consisting of 27 statement items that had been tested for validity and reliability. The results showed that most students responded with